The Application and Patient-Reported Experience of Telephone Consultations in Elective Foot and Ankle Orthopaedic Surgery: 12-Month Follow-up. (May 2022) - Sharma, Aman; Howgate, Daniel; Loizou, Constantinos; Rogers, Mark; Sharp, Robert; Kendal, Adrian; Brown, Rick
Background: Telemedicine offers convenient and affordable health care, overcoming the logistical challenges of face-to-face encounters. Clinicians increasingly relied on telemedicine during the global pandemic. To assess the ongoing role for telemedicine in orthopaedics, we prospectively analyzed the failure rate, safety and patient-reported experience of telephone consultations for 12 months. Methods: 265 telephone Foot/Ankle consultations were conducted in April 2020 and were prospectively analyzed over 12 months. The primary outcome measure was the rate of failed telephone consultations. A consultation was deemed unacceptable if the patient did not answer, if the clinician could not reach a conclusion or if any outcome changed over 12 months. Secondary outcome measures included patient-reported satisfaction and time saved by avoiding a face-to-face visit. Results: A clinical decision was reached in 84% of follow-up telephone consultations and 64% of new patient consultations ( P = 0.001). Sixty-six percent were managed with nonoperative therapies, 16% were discharged, and 11% were added to the waiting list for surgery. The reasons for failing to achieve a clinical decision included failure to contact the patient (12.8%), inappropriate discharge with subsequent rereferral (1.9%), and insufficient clinical information (1.5%). Overall, 84.7% of patients reported that the telephone consultation was highly useful and 71.9% would recommend it to a friend or family member. Patients reported a mean time saving of 120 minutes. Conclusion: Based on our experience, we provide recommended criteria for the safe and practical use of telephone consultations and suggest versatile patient care pathways into which a telephone consultation can be incorporated. Level of Evidence: Level IV, prospective cohort series (noncomparative).